Amphiphilic short peptide modulated wormlike micelle formation with pH and metal ion dual-responsive properties. Issue 116 (6th November 2015) - Wang, Dong; Sun, Yawei; Cao, Meiwen; Wang, Jiqian; Hao, Jingcheng
Abstract : Amphiphilic short peptides (ASPs) and surfactants (C14 DMAO) were employed to prepare dual-responsive wormlike micelles. Abstract : Amphiphilic short peptides (ASPs) and surfactants (C14 DMAO) were employed to prepare wormlike micelles. Herein, ASPs were used to induce wormlike micelle formation. The formation mechanism was investigated by cryo-TEM, FTIR, CD and a rheometer. C14 DMAO could be protonated by a proton which was dissociated from the carboxyl headgroups of ASPs. The mean area of the headgroup would be reduced due to the interaction of protonated cationic surfactants and dissociated anionic ASPs which would lead to wormlike micelle formation. And the length of the wormlike micelles could be modulated by the size of the hydrophobic part of ASPs. The wormlike micelles could also respond to pH and metal ions, respectively. When the pH was regulated from 5.96 to 3.23, the wormlike micelles transformed into a nanofiber network. Nevertheless, when the pH was regulated to over 9, spherical micelles would be formed and the solution would lose its viscoelasticity. When a certain amount of metal salts were added into the wormlike micelle solution with a pH of 5.96, the viscosity of the solution increased significantly. The coordination interaction between metal ions and C14 DMAO was considered as the responsive mechanism. Metal ions with high valence have more obvious effects on wormlike micelles.